Cross-Cultural Learning and Adaptation: Enhancing Madrasah Management in Afghanistan through Insights from Indonesian Madrasah - Habiburrahman Rizapoor (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
Abstract:This article explores the potential applicability of the management practices employed in Madrasah in Indonesia to enhance the management of Madrasah institutions in Afghanistan. Madrasah play a crucial role in shaping the religious education and social fabric of Afghan society, yet they often encounter challenges in effectively implementing modern management principles to optimize their educational outcomes and overall organizational efficiency.Drawing on a comparative approach, this research assesses the key management strategies and systems currently implemented in Islamic schools or Madrasah in Indonesia, a country with a rich tradition of Islamic education and a strong foundation in modern management practices. By analyzing the successful methods employed in these Indonesian educational institutions, this study aims to identify adaptable strategies that can be integrated into the context of Afghanistan's Madrasah management.This research adopts an analytical and comparative approach to examine the organizational structures, pedagogical methodologies, and administrative frameworks of Madrasah both in Afghanistan and Indonesia.The anticipated outcomes of this research are twofold: first, to establish an empirical foundation for understanding the current management practices in Afghan Madrasah, identifying potential challenges and areas for improvement; and second, to present evidence-based recommendations for the integration of successful management techniques from Indonesian Islamic schools. These findings will not only benefit the respective educational institutions but also contribute to the broader discourse on Islamic education management in the global context.The study acknowledges the contextual differences between Afghanistan and Indonesia and the potential cultural and social factors that may influence the implementation of management strategies. Therefore, the research will also explore strategies for adapting and contextualizing the Indonesian management models to suit the unique needs and challenges faced by Afghan Madrasah.The significance of this research lies in its potential to foster improvements in Madrasah education in Afghanistan, thereby contributing to the development of human resources, community building, and overall societal progress. Additionally, the study seeks to promote intercultural exchange and learning between Afghanistan and Indonesia, facilitating cross-border collaboration in the field of Islamic education management.